2023
DOI: 10.34208/jba.v25i1.1798
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliographic Study for Management Control Systems on Journal of Management Accounting Research

Abstract: This study aims to trace the track record of management control system research found in reputable international journals (Journal of Management Accounting Research). To obtain accurate research results, we documented research published during the 2021 period of 45 reputable articles. We found that research in the field of management control systems is a very interesting issue to study. Several previous findings strengthen the trend of management accounting research, especially in the field of MCS which is mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This situation can incur substantial expenses for non-compliant taxpayers (Mikesell & Ross, 2012). Additionally, this study centers its focus on companies that have already demonstrated tax aggressiveness in the years preceding the tax amnesty period, thereby magnifying their feelings of "remorse" and "anxiety" stemming from their prior instances of tax negligence (Cahyono, 2023).…”
Section: Hypothesis Development Tax Aggressive Companies and Tax Amne...mentioning
confidence: 99%
“…This situation can incur substantial expenses for non-compliant taxpayers (Mikesell & Ross, 2012). Additionally, this study centers its focus on companies that have already demonstrated tax aggressiveness in the years preceding the tax amnesty period, thereby magnifying their feelings of "remorse" and "anxiety" stemming from their prior instances of tax negligence (Cahyono, 2023).…”
Section: Hypothesis Development Tax Aggressive Companies and Tax Amne...mentioning
confidence: 99%